Exercise at anaerobic threshold intensity and insulin secretion by isolated pancreatic islets of rats - Machado de Oliveira, Camila Aparecida; Paiva, Mauricio Ferreira [UNESP]; Soares Mota, Clécia Alencar [UNESP]; Ribeiro, Carla [UNESP]; De Almeida Leme, José Alexandre Curiacos [UNESP]; Luciano, Eliete [UNESP]; Rostom de Mello, Maria Alice [UNESP] (Taylor & Francis, 2010)
To evaluate the effect of acute exercise and exercise training at the anaerobic threshold (AT) intensity on aerobic conditioning and insulin secretion by pancreatic islets, adult male Wistar rats were submitted to the lactate minimum test (LMT) for AT determination. Half of the animals were submitted to swimming exercise training (trained), 1 h/day, 5 days/week during 8 weeks, with an overload equivalent to the AT. The other half was kept sedentary. At the end of the experimental period, the rats were submitted to an oral glucose tolerance test and to another LMT. Then, the animals were sacrificed at rest or immediately after 20 minutes of swimming exercise at the AT intensity for pancreatic islets isolation. At the end of the experiment mean workload (% bw) at AT was higher and blood lactate concentration (mmol/L) was lower in the trained than in the control group. Rats trained at the AT intensity showed no alteration in the areas under blood glucose and insulin during OGTT test. Islet insulin content of trained rats was higher than in the sedentary rats while islet glucose uptake did not differ among the groups. The static insulin secretion in response to the high glucose concentration (16.7 mM) of the sedentary group at rest was lower than the sedentary group submitted to the acute exercise and the inverse was observed in relation to the trained groups. physical training at the AT intensity improved the aerobic condition and altered insulin secretory pattern by pancreatic islets. © 2010 Landes Bioscience.
Keywords: Anaerobic threshold; Exercise; Glucose homeostasis; Insulin secretion; Rats; glucose; insulin; lactic acid; aerobic capacity; anaerobic threshold; animal experiment; animal tissue; controlled study; exercise; exercise physiology; glucose blood level; glucose transport; insulin blood level; insulin release; isolated pancreas islet; lactate blood level; male; nonhuman; oral glucose tolerance test; rat; sitting; swimming; training; workload; Anaerobiosis; Animals; Blood Glucose; Cell Separation; Exercise Test; Glucose Tolerance Test; Insulin; Islets of Langerhans; Lactic Acid; Male; Physical Conditioning, Animal; Rats, Wistar; Swimming